Effect Of Organizational Culture And Employee Commitment On Performance In The Office Of PT. Bengkulu Main Branch - Dadang Utuh Ahwat; Ida Angriani; Anzori Tawakal (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to test whether there is an influence of organizational culture and employee commitment on performance at the office of PT. Bank Bengkulu Main Branch, one of the factors that can affect performance is organizational culture. Organizational culture will give identity to members of the organization and individuals, and employee commitment also affects performance. The sample in this study were 56 permanent employees at the PT. Bank Bengkulu Main Branch. By collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing.The results of the multiple linear regression analysis showed Y = 23,359 + 0, 104X1 + 0, 366X2. This describes a positive linear regression direction, meaning that there is a positive influence between X1 (Organizational Culture) and X2 (Employee Commitment) on (Y) Office performance of PT. Bank Bengkulu Main Branch. The magnitude of the coefficient of determination is 0.185. This means that organizational culture and employee commitment affect the performance of the PT. Bank Bengkulu Main Branch of 18.5%, while the remaining 81.5% is influenced by other variables not examined in this study. The test results at a significant level of 0.05 explained that partially organizational culture had no significant effect while employee commitment had a significant effect on performance at the PT. Bank Bengkulu Main Branch. The results of the F test at a significant level of 0.05 explain that organizational culture and employee commitment have a significant simultaneous influence on the performance of the PT. Bank Bengkulu Main Branch.